Flexible strain sensing film, method of making and use thereof
Patent Information
- Application Number
- CN202611190428.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的之一在于提供一种柔性应变传感薄膜,解决现有柔性应变传感薄膜在应用于运动姿态监测时存在的以下技术问题:现有器件为构建有效导电网络需要较高的导电填料含量(通常≥0.25份),导致薄膜柔韧性下降、成本增加,且在超低填料含量下难以形成完整导电网络;同时,现有薄膜材料的应变-电阻响应线性度差、循环稳定性不足,影响监测数据的可靠性
本发明提供的柔性应变传感薄膜,通过采用纳米纤维素与离子液体的复合物作为功能化改性剂,并结合导电填料在热塑性弹性体基体颗粒界面处的选择性分布及隔离导电网络结构的构建,实现了导电填料在极低添加量下的高效利用:该功能化改性剂协同促进导电填料向颗粒界面定向富集并稳定锚定,从而在显著降低导电填料用量的同时,仍能形成连续、均匀且力学性能良好的导电通路,最终达成渗流阈值降低、灵敏度提升与循环稳定性增强的统一效果。
Smart Images

Figure CN122978686A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible sensing materials technology, and in particular to a flexible strain sensing film, its preparation method, and its application. Background Technology
[0002] Flexible electronic skin, a biomimetic sensing technology that can adhere to the human body surface, sense external stimuli, and convert them into electrical signals, has broad application prospects in wearable health monitoring, human-computer interaction, and motion analysis. Motion monitoring devices based on flexible strain sensing mechanisms, by conforming to human joints, can convert deformations caused by limb movement into changes in electrical signals, enabling real-time monitoring of movement posture.
[0003] In existing technologies, flexible strain sensors used for motion monitoring are mostly composed of carbon-based composite materials, metal nanomaterials, or conductive polymers combined with polymer matrices, and have been initially applied to scenarios such as finger bending and joint movement. However, existing flexible strain sensing films still have the following technical problems when applied to motion posture monitoring: First, most devices struggle to achieve a balance between sensitivity, linear response range, and cycle stability. Existing technologies typically increase the conductive filler content to build a dense conductive network to improve sensitivity; however, high filler content leads to decreased film flexibility and increased brittleness and cracking. Conversely, while reducing filler content improves flexibility, it results in an incomplete conductive network and insufficient sensitivity. Second, most existing technologies employ melt blending or solution blending to uniformly disperse the conductive filler in the polymer matrix. This uniform dispersion method requires a relatively high conductive filler content (typically 10-30 parts by weight) to form an effective conductive permeation network, and some conductive filler is encapsulated within the matrix and does not participate in conductivity, resulting in filler waste and impairing the mechanical properties of the matrix. Third, existing film materials lack sufficient interfacial compatibility with skin, leading to slippage, detachment, or skin discomfort with prolonged wear, affecting the stability of monitoring data and user experience.
[0004] According to prior art document 1 (CN110819118B), a conductive elastomer composite material with a matrix of silicone and TPU blend and a conductive filler content of 0.25 to 10 parts is disclosed. The conductive particles are distributed at the interface of the two phases by utilizing the "double percolation" principle to reduce the percolation threshold. However, the conductive filler content in prior art document 1 is not less than 0.25 parts, and its preparation method is limited to conventional melt blending, making it difficult to achieve a highly ordered enrichment of conductive filler at the particle interface, and it does not address the optimization of strain sensing performance at such ultra-low filler content.
[0005] Therefore, developing a flexible electronic skin film that combines high sensitivity, good stability, comfortable wear, and low conductive filler content is of great significance for improving the accuracy and practicality of motion posture monitoring.
[0006] In view of this, the present invention is hereby proposed. Summary of the Invention
[0007] One of the objectives of this invention is to provide a flexible strain sensing film that solves the following technical problems existing in the application of flexible strain sensing films to motion posture monitoring: existing devices require a high content of conductive filler (usually ≥0.25 parts) to construct an effective conductive network, which leads to a decrease in film flexibility and an increase in cost, and it is difficult to form a complete conductive network with ultra-low filler content; at the same time, the strain-resistance response linearity of existing film materials is poor and the cycle stability is insufficient, which affects the reliability of monitoring data.
[0008] The second objective of this invention is to provide a method for preparing the aforementioned flexible strain sensing film.
[0009] The third objective of this invention is to provide the application of the above-mentioned flexible strain sensing film in the preparation of products for monitoring human motion posture.
[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention provides a flexible strain sensing film, comprising a thermoplastic elastomer matrix, a conductive filler, and a functionalized modifier; The functionalized modifier includes a complex of nanocellulose and ionic liquid; The conductive filler is distributed at the particle interface of the thermoplastic elastomer matrix to form an isolated conductive network structure.
[0011] Furthermore, in the functionalized modifier, the mass ratio of the nanocellulose to the ionic liquid is 1:0.5~2; Preferably, the diameter of the nanocellulose is 5~50nm and the aspect ratio is ≥100; Preferably, the ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium hexafluorophosphate. Furthermore, the surface of the nanocellulose is grafted with a silane coupling agent; Preferably, the silane coupling agent includes KH570; Preferably, the grafting rate of the nanocellulose is 0.5% to 15%.
[0012] Furthermore, the conductive filler includes carbon nanotubes and / or silver nanowires; Preferably, the diameter of the carbon nanotubes is 5~20 nm; and / or, The silver nanowires have a diameter of 30-80 nm and a length of 10-50 μm; Preferably, when the conductive filler includes carbon nanotubes and silver nanowires, the mass ratio of the carbon nanotubes to the silver nanowires is 1:0.2~5.
[0013] Furthermore, the hardness range of the thermoplastic elastomer matrix is 60A to 95A.
[0014] Furthermore, by weight, the flexible strain sensing film comprises 90-96 parts of thermoplastic elastomer matrix, 0.03-5 parts of conductive filler, and 0.5-3 parts of functionalized modifier; Preferably, the thickness of the flexible strain sensing film is 50μm to 500μm.
[0015] Furthermore, it also includes additives, said additives including at least one of dispersants, plasticizers, antioxidants and crosslinking agents; Preferably, the auxiliary agent is 2 to 10 parts by weight; Optionally, the dispersant includes at least one of silane coupling agents, titanate coupling agents, and polyvinylpyrrolidone; Optionally, the plasticizer includes at least one of phthalates, phosphates, and citrates; Optionally, the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168; Optionally, the crosslinking agent includes at least one of dicumyl peroxide, benzoyl peroxide, and isocyanate crosslinking agents.
[0016] The present invention also provides a method for preparing the above-mentioned flexible strain sensing thin film, comprising: (a) The conductive filler, the functionalized modifier and the thermoplastic elastomer matrix powder are mixed so that the conductive filler and the functionalized modifier adhere to the particle surface of the thermoplastic elastomer matrix powder to obtain a mixed powder. (b) The mixed powder is subjected to gradient hot pressing molding, so that the thermoplastic elastomer matrix powder particles squeeze and fix the conductive filler to the boundary area of the powder particles during the melt flow process, forming the isolated conductive network structure; (c) Cooling down to obtain the flexible strain sensing film.
[0017] Furthermore, the mixing includes ultrasound-assisted physical blending; Preferably, the ultrasound-assisted physical blending adopts a pulsed ultrasound mode, which includes alternating ultrasound working phases and ultrasound intermittent phases; Preferably, the time ratio of the ultrasonic working phase to the ultrasonic intermittent phase is 1:1; Preferably, the ultrasonic power of the ultrasonic-assisted physical blending is 100~300W, the mixing speed is 300~800 rpm, and the mixing time is 5~20 minutes; Preferably, the gradient hot pressing molding includes: preheating at 100~120℃ for 3~5 minutes, then raising the temperature to 150~200℃, and applying a pressure of 5~20MPa for hot pressing for 5~15 minutes; Preferably, the cooling is reduced to below 60°C.
[0018] Furthermore, the present invention also provides the application of the above-described flexible strain sensing film or the flexible strain sensing film prepared by the above-described preparation method in the preparation of products for monitoring human motion posture.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The flexible strain sensing film provided by this invention utilizes a composite of nanocellulose and ionic liquid as a functional modifier, combined with the selective distribution of conductive fillers at the particle interface of a thermoplastic elastomer matrix and the construction of an isolated conductive network structure. This achieves highly efficient utilization of conductive fillers at extremely low addition levels. The functional modifier synergistically promotes the directional enrichment and stable anchoring of conductive fillers at the particle interface, thereby significantly reducing the amount of conductive fillers used while still forming a continuous, uniform, and mechanically sound conductive pathway. Ultimately, this achieves a unified effect of reduced percolation threshold, increased sensitivity, and enhanced cycle stability.
[0020] The method for preparing flexible strain sensing films provided by this invention achieves controllable construction of the spatial distribution of conductive networks through a specific process path. This avoids network redundancy and performance fluctuations caused by the random dispersion or agglomeration of conductive fillers within the matrix in traditional blending processes, and overcomes the problems of weak filler bonding and easy detachment in simple surface coating processes. Thus, without increasing the total amount of conductive fillers, a stable and uniform isolated conductive network structure is precisely constructed, while simultaneously achieving enhanced interfacial bonding strength between the conductive fillers and the boundaries of thermoplastic elastomer matrix particles.
[0021] The aforementioned flexible strain sensing film, which features an isolated conductive network structure and synergistic regulation of interface behavior by functional modifiers, can be directly applied to human motion posture monitoring scenarios to achieve high-fidelity, low-intrusion, and long-term stable acquisition of physiological and mechanical signals. Attached Figure Description To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0022] Figure 1 A schematic diagram of motion posture detection provided in an embodiment of the present invention, showing a flexible strain sensing film attached to the wrist. Figure 2 This invention provides signal diagrams of the movement postures of professional and non-professional athletes under different movements during exercise, as provided in an embodiment of the invention. Figure 3 The image shows a cross-sectional SEM image of the flexible strain sensing film provided in an embodiment of the present invention. Detailed Implementation
[0023] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] According to one aspect of the present invention, a flexible strain sensing film is provided, comprising a thermoplastic elastomer matrix, a conductive filler, and a functionalized modifier; The functionalized modifier includes a complex of nanocellulose and ionic liquid; The conductive filler is distributed at the particle interface of the thermoplastic elastomer matrix to form an isolated conductive network structure.
[0026] The core technical concept of this invention lies in the fact that, based on the construction of an isolated conductive network structure, nanocellulose and ionic liquid composites are introduced for the first time as functional modifiers. Through multiple synergistic effects, efficient interface enrichment, conductive network optimization, and significant improvement in sensing performance are achieved at ultra-low concentrations (as low as 0.03 parts) of conductive filler. Specifically: (1) Dispersion and Synergy: Nanocellulose can be adsorbed onto the surface of conductive filler to form nanocellulose-conductive filler composite units; ionic liquid, as a surfactant, can reduce the surface energy of thermoplastic elastomer matrix powder and promote the migration of composite units to the surface of thermoplastic elastomer matrix particles. The synergistic effect of the two effectively inhibits the agglomeration of conductive filler, so that conductive filler can still be uniformly and densely adhered to the interface of thermoplastic elastomer matrix particles even at extremely low content.
[0027] (2) Interface bridging: Nanocellulose acts as a molecular bridge during hot pressing. Its surface hydroxyl groups form hydrogen bonds with the urethane groups of thermoplastic elastomer. At the same time, ionic liquid promotes the migration and rearrangement of thermoplastic elastomer molecular chains at the interface, significantly enhancing the interfacial bonding force between the conductive filler and the thermoplastic elastomer matrix, thereby firmly locking the conductive network at the particle boundary.
[0028] (3) Optimization of conductive network: The insulating properties of nanocellulose can regulate the contact resistance between conductive fillers, so that the strain-resistance response curve changes from the traditional exponential type to a piecewise linear response with higher linearity, which greatly improves the calibrability and repeatability of the sensor.
[0029] In some preferred embodiments, the mass ratio of the nanocellulose to the ionic liquid in the functionalized modifier is 1:0.5 to 2; for example, it can be, but is not limited to, 1:0.5, 1:1, 1:1.5 or 1:2.
[0030] In some preferred embodiments, the nanocellulose has a diameter of 5-50 nm and an aspect ratio ≥100. Further limiting the size and high aspect ratio of the nanocellulose synergistically enhances its coating ability and interfacial bridging efficiency on the conductive filler surface: the small diameter makes it easier to penetrate and adsorb onto the curved surfaces and gaps of conductive fillers such as carbon nanotubes and silver nanowires; the high aspect ratio provides a larger specific surface area and better network entanglement ability, thereby more effectively anchoring the conductive filler to the thermoplastic elastomer matrix particle interface during subsequent preparation and inhibiting filler agglomeration. Ultimately, a highly interconnected and highly strain-response-consistent isolated conductive network structure is stably constructed with extremely low filler content. In some preferred embodiments, the ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium hexafluorophosphate.
[0031] In some preferred embodiments, the surface of the nanocellulose is grafted with a silane coupling agent. By grafting a silane coupling agent onto the surface of the nanocellulose, a covalent bond bridge can be constructed between the nanocellulose and the thermoplastic elastomer matrix. The organic functional groups at the ends can then physically entangle or chemically react with the polar groups in the thermoplastic elastomer molecular chains, thereby significantly enhancing the bonding strength at the interface between the nanocellulose, the ionic liquid functionalized modifier, and the thermoplastic elastomer matrix particles. This further ensures that the conductive filler is stably fixed in the particle boundary region during preparation, ultimately improving the mechanical durability and long-term stability of the resistive response of the isolated conductive network structure. Typically, the silane coupling agent includes KH570.
[0032] In some preferred embodiments, the grafting rate of the nanocellulose is 0.5% to 15%, for example, but not limited to 0.5%, 1%, 2%, 5%, 8%, 10%, 12% or 15%.
[0033] In some preferred embodiments, the conductive filler comprises carbon nanotubes and / or silver nanowires. Carbon nanotubes have a high aspect ratio and excellent long-range electron transport capability, which is beneficial for forming a through conductive pathway; silver nanowires have high intrinsic conductivity, good flexibility and low contact resistance, which is beneficial for improving the strain adaptability and signal response speed of local conductive nodes.
[0034] In some preferred embodiments, the diameter of the carbon nanotubes is 5-20 nm, for example, but not limited to 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, or 20 nm; and / or, The silver nanowires have a diameter of 30-80 nm and a length of 10-50 μm; In some preferred embodiments, when the conductive filler comprises carbon nanotubes and silver nanowires, the mass ratio of the carbon nanotubes to the silver nanowires is 1:0.2 to 5, for example, but not limited to 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4, or 1:5. The combined use of these two materials can achieve a skeleton-node synergistic configuration of the conductive network at ultra-low total content: carbon nanotubes form a stable backbone network, while silver nanowires bridge micro-gaps and buffer deformation stress, thereby significantly improving the connectivity stability, resistance change sensitivity, and response linearity of the isolated conductive network during dynamic stretching, avoiding problems such as network breakage, contact failure, or nonlinear saturation that easily occur in single filler systems at low content.
[0035] In some preferred embodiments, the hardness range of the thermoplastic elastomer matrix is 60A to 95A. This specific hardness range ensures that the film fully conforms to the curved surfaces of human joints and can withstand repeated large deformations, while also balancing sufficient rebound and mechanical durability. When the hardness is below 60A, permanent deformation or slippage is likely to occur, leading to sensor position shift and signal drift; when the hardness is above 95A, it is difficult to conform to the skin's microstructure, resulting in decreased wearing comfort.
[0036] In some preferred embodiments, the flexible strain sensing film comprises, by weight, 90-96 parts of a thermoplastic elastomer matrix, for example, but not limited to 90, 92, 94, or 96 parts; 0.03-5 parts of a conductive filler, for example, but not limited to 0.03, 0.1, 0.5, 1, 2, 3, 4, or 5 parts; and 0.5-3 parts of a functional modifier, for example, but not limited to 0.5, 1, 2, or 3 parts.
[0037] Because the thermoplastic elastomer matrix particles remain in a pure elastomeric state, free of conductive fillers and functional modifiers, the overall flexibility, resilience, and tensile properties of the film are perfectly maintained. Combined with the soft feel resulting from the ultra-low filler content, this significantly improves long-term wearing comfort.
[0038] In some preferred embodiments, the thickness of the flexible strain sensing film is 50 μm to 500 μm, for example, but not limited to 50 μm, 100 μm, 200 μm, 300 μm, 400 μm or 500 μm.
[0039] In some preferred embodiments, the additive further includes at least one of a dispersant, a plasticizer, an antioxidant, and a crosslinking agent. Typically, the additive is 2 to 10 parts by weight, for example, but not limited to 2, 3, 4, 5, 6, 7, 8, 9, or 10 parts.
[0040] In some alternative embodiments, the dispersant includes at least one of silane coupling agents, titanate coupling agents, and polyvinylpyrrolidone.
[0041] In some alternative embodiments, the plasticizer includes at least one of phthalates, phosphates, and citrates.
[0042] In some alternative embodiments, the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0043] In some alternative embodiments, the crosslinking agent includes at least one of dicumyl peroxide, benzoyl peroxide, and isocyanate crosslinking agents.
[0044] According to a second aspect of the present invention, a method for preparing the above-described flexible strain sensing thin film is provided, comprising: (a) The conductive filler, the functionalized modifier and the thermoplastic elastomer matrix powder are mixed so that the conductive filler and the functionalized modifier adhere to the particle surface of the thermoplastic elastomer matrix powder to obtain a mixed powder. (b) The mixed powder is subjected to gradient hot pressing molding, so that the thermoplastic elastomer matrix powder particles squeeze and fix the conductive filler to the boundary area of the powder particles during the melt flow process, forming the isolated conductive network structure; (c) Cooling down to obtain the flexible strain sensing film.
[0045] The method for preparing flexible strain sensing films provided by this invention achieves controllable construction of the spatial distribution of conductive networks through a specific process path. This avoids network redundancy and performance fluctuations caused by the random dispersion or agglomeration of conductive fillers within the matrix in traditional blending processes, and overcomes the problems of weak filler bonding and easy detachment in simple surface coating processes. Thus, without increasing the total amount of conductive fillers, a stable and uniform isolated conductive network structure is precisely constructed, while simultaneously achieving enhanced interfacial bonding strength between the conductive fillers and the boundaries of thermoplastic elastomer matrix particles.
[0046] In some preferred embodiments, the mixing includes ultrasound-assisted physical blending.
[0047] In some preferred embodiments, the ultrasound-assisted physical blending employs a pulsed ultrasound mode, which includes alternating ultrasound working phases and ultrasound intermittent phases, wherein the time ratio of the ultrasound working phases to the ultrasound intermittent phases is 1:1.
[0048] In some preferred embodiments, the ultrasonic power of the ultrasonic-assisted physical blending is 100~300W, for example, but not limited to 100W, 120W, 150W, 180W, 200W, 220W, 250W, 280W or 300W; the mixing speed is 300~800 rpm, for example, but not limited to 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm; the mixing time is 5~20 minutes, for example, but not limited to 5 minutes, 8 minutes, 10 minutes, 12 minutes, 15 minutes, 18 minutes or 20 minutes.
[0049] In some preferred embodiments, the gradient hot pressing molding includes: preheating at 100~120°C (e.g., 100°C, 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C or 120°C) for 3~5 minutes (e.g., 3 minutes, 4 minutes or 5 minutes), then raising the temperature to 150~200°C (e.g., 150°C, 160°C, 170°C, 180°C, 190°C or 200°C), and applying a pressure of 5~20 MPa (e.g., 5 MPa, 8 MPa, 10 MPa, 12 MPa, 15 MPa, 18 MPa or 20 MPa) for 5~15 minutes (e.g., 5 minutes, 8 minutes, 10 minutes, 12 minutes or 15 minutes).
[0050] This invention utilizes a specific process combining ultrasonic-assisted low-speed blending with gradient hot pressing to increase the coverage of conductive filler on the surface of thermoplastic elastomer matrix particles from 65% in conventional low-speed blending to over 92%. The cavitation effect of ultrasound promotes the formation of a ternary assembly of nanocellulose-ionic liquid-conductive filler and drives its enrichment on the surface of thermoplastic elastomer matrix particles, thereby constructing a complete and uniform isolated conductive network even with an ultra-low filler content of 0.03 parts.
[0051] In some preferred embodiments, the cooling is reduced to below 60°C.
[0052] According to a third aspect of the present invention, the application of the above-described flexible strain sensing film or the flexible strain sensing film prepared by the above-described preparation method in the preparation of products for monitoring human motion posture is provided.
[0053] The flexible strain sensing film provided by this invention can be used in the fabrication of human motion posture monitoring products, achieving a precise match between sensing functions and ergonomic requirements. Its ultra-low conductive filler content, combined with a high-hardness thermoplastic elastomer matrix, endows the film with excellent mechanical compatibility, seamless fit, and resistance to sweat / deformation slippage. Meanwhile, the isolated conductive network maintains high linearity and repeatability across the micro-strain to large-strain range, enabling the acquired resistance signals to accurately, stably, and calibratedly map joint angle changes, muscle activation timing, and gait phase characteristics. This supports multi-level motion monitoring needs, from refined analysis of professional athletes' movements to real-time feedback of fitness postures for the general public, overcoming the technical bottlenecks of existing flexible sensors that hinder clinical / consumer applications due to signal distortion, discomfort during wear, or insufficient long-term stability.
[0054] The present invention will be further illustrated below through examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market. The thermoplastic polyurethane elastomer powder (TPU): BASF Elastollan® C; nanocellulose: Nanjing Tianlu Nano TL-014; silver nanowires: Bailingwei Technology; ionic liquid: Moni Chemical; plasticizer: acetylacetic tributyl citrate (ATBC), McLean; silane coupling agent: KH-570; antioxidant: 1010.
[0055] Example 1 95 parts of thermoplastic polyurethane elastomer powder (hardness 85A), 3 parts of carbon nanotubes (diameter 10nm), 1.5 parts of functionalized modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate in a 1:1 mass ratio, wherein the nanocellulose is grafted with silane coupling agent KH570 at a grafting rate of 8%), and 2 parts of silane coupling agent were subjected to ultrasonic-assisted low-speed physical blending. The ultrasonic power was 150W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 600 rpm, and the mixing time was 12 minutes, ensuring that the conductive filler and functionalized modifier were uniformly adhered to the surface of the thermoplastic polyurethane elastomer powder particles, resulting in a mixed powder. The mixed powder was placed on a flat vulcanizing machine, preheated at 110℃ for 4 minutes, then heated to 180℃, and hot-pressed at 10MPa for 10 minutes, controlling the mold gap at 200μm. The pressure was maintained and the temperature was lowered to below 60℃ to obtain a flexible strain-sensing film.
[0056] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10, volume ratio) at a mass ratio of 1:0.4, and the mixture was stirred and reacted in a water bath at 80°C for 12 hours. After the reaction was completed, the product was centrifuged at 8000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0057] Example 2 96 parts of thermoplastic polyurethane elastomer powder (hardness 75A), 2.5 parts of graphene, 2 parts of functionalized modifier (composed of nanocellulose and ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate at a mass ratio of 1:1.5, wherein the nanocellulose is grafted with silane coupling agent KH570 with a grafting rate of 5%), and 1 part of titanate coupling agent were ultrasonically assisted low-speed physical blending. The ultrasonic power was 120W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 500 rpm, and the mixing time was 15 minutes, ensuring that the conductive filler and functionalized modifier were uniformly adhered to the surface of the thermoplastic polyurethane elastomer powder particles, resulting in a mixed powder. The mixed powder was placed on a flat vulcanizing machine, preheated at 105℃ for 5 minutes, then heated to 170℃, and hot-pressed at 12MPa for 8 minutes, controlling the mold gap at 150μm. The pressure was maintained and the temperature was lowered to below 60℃ to obtain a flexible strain sensing film.
[0058] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10, volume ratio) at a mass ratio of 1:0.2, and the mixture was stirred and reacted in a water bath at 80°C for 12 hours. After the reaction was completed, the product was centrifuged at 8000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0059] Example 3 98 parts of thermoplastic polyurethane elastomer powder (hardness 90A), 1.5 parts of silver nanowires (50 nm in diameter and 30 μm in length), 1 part of functional modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate at a mass ratio of 1:0.8, wherein the nanocellulose is grafted with silane coupling agent KH570 with a grafting rate of 12%), and 0.5 parts of polyvinylpyrrolidone were subjected to ultrasonic-assisted low-speed physical blending. The ultrasonic power was 200 W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 400 rpm, and the mixing time was 10 minutes. This ensured that the conductive filler and functional modifier were uniformly adhered to the surface of the thermoplastic polyurethane elastomer powder particles, resulting in a mixed powder. The mixed powder is placed on a flat vulcanizing machine, preheated at 115°C for 3 minutes, then heated to 160°C, and hot-pressed at 8MPa for 12 minutes. The mold gap is controlled at 300μm, and the pressure is maintained and the temperature is lowered to below 60°C to obtain a flexible strain sensing film.
[0060] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10 volume ratio) at a mass ratio of 1:0.5, and the mixture was stirred and reacted in a water bath at 80°C for 24 hours. After the reaction was completed, the product was centrifuged at 8000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0061] Example 4 97 parts of thermoplastic polyurethane elastomer powder (hardness 80A), 2 parts of carbon black, 2.5 parts of functionalized modifier (composed of nanocellulose and ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate in a mass ratio of 1:2, wherein the nanocellulose is grafted with silane coupling agent KH570 with a grafting rate of 3%), and 1 part of silane coupling agent were subjected to ultrasonic-assisted low-speed physical blending. The ultrasonic power was 180W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 700 rpm, and the mixing time was 8 minutes, ensuring that the conductive filler and functionalized modifier were uniformly adhered to the surface of the thermoplastic polyurethane elastomer powder particles, resulting in a mixed powder. The mixed powder was placed on a flat vulcanizing machine, preheated at 100℃ for 5 minutes, then heated to 175℃, and hot-pressed at 9MPa for 10 minutes, controlling the mold gap at 250μm. The pressure was maintained and the temperature was lowered to below 60℃ to obtain a flexible strain sensing film.
[0062] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10, volume ratio) at a mass ratio of 1:0.1, and the mixture was stirred and reacted in a water bath at 80°C for 24 hours. After the reaction was completed, the product was centrifuged at 8000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0063] Example 5 99 parts of thermoplastic polyurethane elastomer powder (hardness 95A), 0.5 parts of liquid metal (gallium indium alloy), 0.8 parts of functionalized modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate at a mass ratio of 1:0.5, wherein the nanocellulose is grafted with silane coupling agent KH570 with a grafting rate of 15%), and 0.5 parts of plasticizer acetylacetic acid tributyl ester (ATBC) were subjected to ultrasonic-assisted low-speed physical blending. The ultrasonic power was 250W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 800 rpm, and the mixing time was 6 minutes, so that the conductive filler and functionalized modifier were uniformly adhered to the surface of the thermoplastic polyurethane elastomer powder particles to obtain a mixed powder. The mixed powder is placed on a flat vulcanizing machine, preheated at 120°C for 3 minutes, then heated to 185°C, and hot-pressed at 11MPa for 7 minutes. The mold gap is controlled at 100μm, and the pressure is maintained and the temperature is lowered to below 60°C to obtain a flexible strain sensing film.
[0064] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10, volume ratio) at a mass ratio of 1:0.5, and the mixture was stirred and reacted in a water bath at 80°C for 24 hours. After the reaction was completed, the product was centrifuged at 10,000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0065] Example 6 96 parts of thermoplastic polyurethane elastomer powder (hardness 85A) were mixed with 0.03 parts of carbon nanotubes (diameter 10 nm), 0.01 parts of silver nanowires (diameter 50 nm, length 30 μm), 0.5 parts of functionalizing modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate in a 1:1 mass ratio, wherein the nanocellulose was grafted with silane coupling agent KH570 at a grafting rate of 10%), and 3.5 parts of additives (silane coupling agent KH570: 2 parts, antioxidant 1010: 0.5 parts, plasticizer acetylthiol tributyl citrate: 1 part) by ultrasonic-assisted low-speed physical blending. The ultrasonic power was 200W, the pulse mode was used (5 seconds on, 5 seconds off), the mixing speed was 500 rpm, and the mixing time was 15 minutes.
[0066] The mixed powder is placed on a flat vulcanizing machine, preheated at 110°C for 4 minutes, then heated to 180°C, and hot-pressed at 12MPa for 10 minutes. The mold gap is controlled at 150μm, and the pressure is maintained while the temperature is lowered to 50°C to obtain a flexible strain sensing film.
[0067] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10 volume ratio) at a mass ratio of 1:0.4, and the mixture was stirred and reacted in a water bath at 70°C for 24 hours. After the reaction was completed, the product was centrifuged at 10,000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0068] Example 7 90 parts of thermoplastic polyurethane elastomer powder (hardness 95A) were mixed with 0.005 parts of carbon nanotubes (10 nm in diameter), 0.025 parts of silver nanowires (50 nm in diameter and 30 μm in length), 0.5 parts of functionalizing modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate at a mass ratio of 1:2, wherein the nanocellulose was grafted with silane coupling agent KH570 at a grafting rate of 0.5%), and 10 parts of additives (6 parts of silane coupling agent KH570, 1.5 parts of antioxidant 1010, and 2.5 parts of plasticizer tributyl acetylacetate). The ultrasonic power was 100 W, using pulse mode (5 seconds on, 5 seconds off), the mixing speed was 800 rpm, and the mixing time was 5 minutes.
[0069] The mixed powder is placed on a flat vulcanizing machine, preheated at 120°C for 3 minutes, then heated to 200°C, and hot-pressed at 5MPa for 15 minutes. The mold gap is controlled at 500μm, and the temperature is lowered to 60°C while maintaining the pressure to obtain a flexible strain sensing film.
[0070] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10 v / v) at a mass ratio of 1:0.1 and reacted under stirring in a water bath at 70°C for 12 hours. After the reaction was completed, the product was centrifuged at 8000 rpm for 20 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 24 hours to obtain KH570-grafted modified nanocellulose.
[0071] Example 8 96 parts of thermoplastic polyurethane elastomer powder (hardness 60A) were mixed with 4 parts of carbon nanotubes (diameter 10nm), 1 part of silver nanowires (diameter 50nm, length 30μm), 3 parts of functional modifier (composed of nanocellulose and ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate at a mass ratio of 1:0.5, wherein the nanocellulose was grafted with silane coupling agent KH570 with a grafting rate of 15%), and 2 parts of additives (silane coupling agent KH570: 1 part, antioxidant 1010: 0.3 parts, plasticizer acetylthiol tributyl citrate: 0.7 parts) by ultrasonic-assisted low-speed physical blending. The ultrasonic power was 300W, the pulse mode was used (5 seconds on, 5 seconds off), the mixing speed was 300 rpm, and the mixing time was 20 minutes.
[0072] The mixed powder is placed on a flat vulcanizing machine, preheated at 100°C for 5 minutes, then heated to 150°C, and hot-pressed at 20MPa for 5 minutes. The mold gap is controlled at 50μm, and the temperature is lowered to 60°C while maintaining the pressure to obtain a flexible strain sensing film.
[0073] The method of grafting and modifying nanocellulose with silane coupling agent KH570 is described in Example 5.
[0074] Example 9 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 in that the mass ratio of nanocellulose to ionic liquid in the functionalized modifier is 1:0.2.
[0075] Example 10 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 only in that the mass ratio of nanocellulose to ionic liquid in the functionalized modifier is 1:3.
[0076] Example 11 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 only in that the nanocellulose is not grafted with silane coupling agent KH570 (grafting rate is 0).
[0077] Example 12 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 only in that the grafting rate of nanocellulose is 20%.
[0078] The method for grafting and modifying nanocellulose with silane coupling agent KH570 is as follows: Nanocellulose and silane coupling agent KH570 were added to a mixed solvent of ethanol / water (90:10 volume ratio) at a mass ratio of 1:0.5, and the mixture was stirred and reacted in a water bath at 80°C for 24 hours. After the reaction was completed, the product was centrifuged at 10,000 rpm for 15 minutes, the supernatant was removed, and the product was washed five times with anhydrous ethanol to remove unreacted silane coupling agent. Finally, the obtained product was placed in a vacuum oven and dried at 80°C for 12 hours to obtain KH570-grafted modified nanocellulose.
[0079] Example 13 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 only in that the hardness of the thermoplastic polyurethane elastomer powder is 50A.
[0080] Example 14 This embodiment provides a flexible strain sensing film, which differs from Embodiment 6 only in that the hardness of the thermoplastic polyurethane elastomer powder is 100A.
[0081] Comparative Example 1 The difference between this comparative example and Example 1 is that no conductive filler was added, and only 100 parts of thermoplastic polyurethane elastomer powder were used to prepare the film using the same process.
[0082] Comparative Example 2 The difference between this comparative example and Example 2 is that the conductive filler content is 8 parts, that is: 92 parts of thermoplastic polyurethane elastomer powder, 8 parts of graphene, and 1 part of titanate coupling agent are used to prepare a film according to the same process.
[0083] Comparative Example 3 The difference between this comparative example and Example 8 is that physical blending is not performed. Instead, the conductive filler is directly spread on the surface of the thermoplastic polyurethane elastomer powder and then hot-pressed: the mixed powder is placed on a flat vulcanizing machine, preheated at 100°C for 5 minutes, then heated to 150°C, and hot-pressed at 20MPa for 5 minutes, controlling the mold gap at 50μm. The pressure is maintained and the temperature is lowered to 60°C to obtain a flexible electronic skin film. That is, 98 parts of thermoplastic polyurethane elastomer powder, 1.5 parts of silver nanowires, 1 part of functional modifier, and 0.5 parts of polyvinylpyrrolidone are directly hot-pressed without mixing.
[0084] Comparative Example 4 The difference between this comparative example and Example 6 is that only nanocellulose (without ionic liquid) is added to the functionalized modifier, namely: 96 parts TPU powder, 0.03 parts carbon nanotubes, 0.01 parts silver nanowires, 0.5 parts nanocellulose (without ionic liquid composite), and 3.5 parts additives. The same ultrasonic-assisted low-speed blending and hot-pressing process is used to prepare the film.
[0085] Comparative Example 5 The difference between this comparative example and Example 6 is that only ionic liquid (without nanocellulose) is added to the functionalized modifier, namely: 96 parts TPU powder, 0.03 parts carbon nanotubes, 0.01 parts silver nanowires, 0.5 parts ionic liquid (1-ethyl-3-methylimidazolium tetrafluoroborate), and 3.5 parts additives. The same ultrasonic-assisted low-speed blending and hot-pressing process is used to prepare the film.
[0086] Comparative Example 6 The difference between this comparative example and Example 6 is that no functional modifier is added.
[0087] Comparative Example 7 50 parts of thermoplastic polyurethane elastomer (TPU, BASF 45A), 50 parts of methyl vinyl silicone rubber (SiR, Zhonglan Chenguang 110-2), 2.5 parts of compatibilizer PDMS-PB-PU, and 2 parts of compatibilizer PDMS-PEG-PU were sequentially added to a hot roll mill for plasticizing at a mixing temperature of 180℃. Then, 0.3 parts of graphene oligolamellae (5-20 layers, layer thickness 1.5-5 nm, transverse dimension 1-10 μm) were added and mixed. After homogeneous mixing, 0.25 parts of vulcanizing agent DCP were added at 40℃, and the mixture was sheeted. The resulting compound was then pressed and vulcanized on an electrically heated flat vulcanizing machine at 170℃, and cold-pressed to obtain a conductive elastomer composite material.
[0088] Comparative Example 8 The difference between this comparative example and Example 6 is that melt blending is used instead of ultrasonic-assisted physical blending, so that the conductive filler is uniformly dispersed inside the thermoplastic elastomer matrix without forming an isolated conductive network structure. That is, the raw materials of the formula are added to a mixer and melt-blended at 180°C for 15 minutes to uniformly disperse the conductive filler in the matrix. After discharge, the material is crushed and then shaped using the same gradient hot pressing process as in Example 6 (preheating at 110°C for 4 minutes, hot pressing at 180°C and 12MPa for 10 minutes, mold gap of 150μm, holding pressure and cooling to 50°C) to obtain a flexible strain sensing film.
[0089] Comparative Example 9 The only difference between this comparative example and Example 6 is the hot pressing procedure: the preheating gradient stage is omitted, and hot pressing is performed directly with increased temperature. That is, the mixed powder is prepared according to the exact same formula and ultrasonic-assisted low-speed physical blending process as in Example 6; the mixed powder is placed on a flat vulcanizing machine, and without a preheating stage, it is directly hot-pressed at 12MPa pressure at 180°C for 10 minutes, with the mold gap controlled at 150μm, and the pressure is maintained while the temperature is lowered to 50°C to obtain a flexible strain sensing film.
[0090] Experimental Example Percolation threshold: With fixed matrix and modifier dosages, the amount of conductive filler added is gradually varied (0.005 to 1 part). The volume resistivity of each sample is measured (four-probe method, Keithley 2400). A log(resistivity)-log(filler content) curve is plotted, and the content corresponding to the inflection point of the curve is the percolation threshold.
[0091] Sensitivity coefficient GF: Cut the film into strips of 30mm×5mm, coat both ends with conductive silver paste and lead out wires, fix them in a tensile testing machine (gauge length 20mm, tensile speed 50mm / min), and record the strain ε and the rate of change of resistance ΔR / R0 simultaneously. Plot the ΔR / R0-ε curve, and the slope of the curve is GF.
[0092] linearity R 2The least squares method is used to perform linear fitting on the above ΔR / R0-ε curve, and the fitting coefficient is R. 2 (The closer to 1, the better).
[0093] Table 1. Composition and motion monitoring effects of flexible electronic skin films with different formulations.
[0094] The above data illustrates: (1) According to the data of Examples 1 to 8, the use of carbon nanotubes and silver nanowires combined with functionalized modifiers can reduce the percolation threshold to below 0.01 parts with an ultra-low filler content of 0.03 to 0.04 parts, and the sensitivity coefficient reaches 58.6, which is significantly better than the conventional content scheme of single conductive filler in Examples 1 to 5. This shows that the synergy between functionalized modifiers and the isolation conductive network structure realizes the efficient utilization of conductive filler.
[0095] (2) According to the data from Example 6 and Comparative Examples 4-6, the GF drops to 15.2 when nanocellulose is added alone, and to 18.4 when ionic liquid is added alone. When no functional modifier is added at all, the GF is only 8.6 and the linearity R 2 The value dropped to 0.72, indicating that nanocellulose and ionic liquid have a synergistic effect in promoting the enrichment of conductive fillers at the particle interface.
[0096] (3) According to the data of Example 6 and Comparative Examples 3, 8 and 9, the specific preparation method of ultrasonic-assisted physical blending combined with gradient hot pressing is the key to further constructing a stable and uniform isolated conductive network structure.
[0097] (4) According to the data of Examples 6 and 9-14, the schemes with functionalized modifier mass ratio, nanocellulose grafting rate and matrix hardness outside the preferred range can still achieve motion posture monitoring, but the sensitivity and linearity are significantly lower than those within the preferred range, indicating that the preferred range of the present invention plays an important role in obtaining excellent sensing performance.
[0098] In summary, this invention achieves a balance between reduced percolation threshold, improved sensitivity, and enhanced linear response at ultra-low conductive filler content through the synergistic effect of functionalized modifiers, isolated conductive network structures, and specific preparation processes.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A flexible strain sensing film, characterized in that, It includes thermoplastic elastomer matrix, conductive filler, and functionalized modifier; The functionalized modifier includes a complex of nanocellulose and ionic liquid; The conductive filler is distributed at the particle interface of the thermoplastic elastomer matrix to form an isolated conductive network structure.
2. The flexible strain sensing film according to claim 1, characterized in that, In the functionalized modifier, the mass ratio of the nanocellulose to the ionic liquid is 1:0.5~2; Preferably, the diameter of the nanocellulose is 5~50nm and the aspect ratio is ≥100; Preferably, the ionic liquid comprises at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate or 1-butyl-3-methylimidazolium hexafluorophosphate.
3. The flexible strain sensing film according to claim 2, characterized in that, The surface of the nanocellulose is grafted with a silane coupling agent. Preferably, the silane coupling agent includes KH570; Preferably, the grafting rate of the nanocellulose is 0.5% to 15%.
4. The flexible strain sensing film according to claim 1, characterized in that, The conductive filler includes carbon nanotubes and / or silver nanowires; Preferably, the diameter of the carbon nanotubes is 5~20 nm; and / or, The silver nanowires have a diameter of 30-80 nm and a length of 10-50 μm; Preferably, when the conductive filler includes carbon nanotubes and silver nanowires, the mass ratio of the carbon nanotubes to the silver nanowires is 1:0.2~5.
5. The flexible strain sensing film according to claim 1, characterized in that, The hardness range of the thermoplastic elastomer matrix is 60A to 95A.
6. The flexible strain sensing film according to any one of claims 1-5, characterized in that, By weight, the flexible strain sensing film comprises 90-96 parts of thermoplastic elastomer matrix, 0.03-5 parts of conductive filler, and 0.5-3 parts of functionalized modifier; Preferably, the thickness of the flexible strain sensing film is 50μm to 500μm.
7. The flexible strain sensing film according to claim 1, characterized in that, It also includes additives, which include at least one of dispersants, plasticizers, antioxidants and crosslinking agents; Preferably, the auxiliary agent is 2 to 10 parts by weight; Optionally, the dispersant includes at least one of silane coupling agents, titanate coupling agents, and polyvinylpyrrolidone; Optionally, the plasticizer includes at least one of phthalates, phosphates, and citrates; Optionally, the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168; Optionally, the crosslinking agent includes at least one of dicumyl peroxide, benzoyl peroxide, and isocyanate crosslinking agents.
8. A method for preparing a flexible strain-sensing thin film as described in any one of claims 1-7, characterized in that, include: (a) The conductive filler, the functionalized modifier and the thermoplastic elastomer matrix powder are mixed so that the conductive filler and the functionalized modifier adhere to the particle surface of the thermoplastic elastomer matrix powder to obtain a mixed powder. (b) The mixed powder is subjected to gradient hot pressing molding, so that the thermoplastic elastomer matrix powder particles squeeze and fix the conductive filler to the boundary area of the powder particles during the melt flow process, forming the isolated conductive network structure; (c) Cooling down to obtain the flexible strain sensing film.
9. The preparation method according to claim 8, characterized in that, The blending includes ultrasound-assisted physical blending; Preferably, the ultrasound-assisted physical blending adopts a pulsed ultrasound mode, which includes alternating ultrasound working phases and ultrasound intermittent phases; Preferably, the time ratio of the ultrasonic working phase to the ultrasonic intermittent phase is 1:1; Preferably, the ultrasonic power of the ultrasonic-assisted physical blending is 100~300W, the mixing speed is 300~800 rpm, and the mixing time is 5~20 minutes; Preferably, the gradient hot pressing molding includes: preheating at 100~120℃ for 3~5 minutes, then raising the temperature to 150~200℃, and applying a pressure of 5~20MPa for hot pressing for 5~15 minutes; Preferably, the cooling is reduced to below 60°C.
10. The application of the flexible strain sensing film according to any one of claims 1-7 or the flexible strain sensing film prepared by the preparation method according to claim 8 or 9 in the preparation of products for monitoring human motion posture.
Citation Information
Patent Citations
A conductive elastomer composite material for wearable devices and its preparation method
CN110819118B